PROSES PEMURNIAN FRAKSI KAYA RHODINOL MINYAK SEREH WANGI MENGGUNAKAN SPINNING BAND DISTILLATION - Arum Nur Fitrah; Meika Syahbana Rusli; Dwi Setyaningsih; Arief Riyanto; Nur Hidayati (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Indonesia, as one of the biggest countries which supplies citronella oil, has a high potential to produce natural rhodinol. Recent studies on rhodinol purification using fractional and mollecular distillation showed the difficulty of obtaining high purity and yield. The objective of this study was to determine the method of spinning band distillation to purify rhodinol regarding reflux ratio and vaporization temperature. Citronella oil was divided into three fractions according to its boiling points. The volume of each fraction was estimated by its ratio (according to GC analysis) to the feed volume: F1 (components before rhodinol) 21.73%, F2 (rhodinol) 61.7%, and residue 15.82%. Initial research established the best conditioning before the purification process was 3 mmHg of pressure, equilibration started at 160oC in 30 minutes, and 18–17% of heat rate, as these created the stability of the vapor temperature. The levels of reflux ratio were 3:1 and 5:1, while the evaporation temperatures of rhodinol were 230oC and 235 oC. Reflux ratio of 5:1 at 230oC obtained the highest purity (81.30%) and the highest yield (72.94%). Equilibration and reflux ratio allowed rectification inside the column because the spinning band homogenized the vapour molecules by its downwards flow and wiped the reflux on the inner surface, which in turn caused the molecules with a lower boiling point to evaporate gradually. Meanwhile the other yields were 79.81% (3:1 at 230 oC), 80.53% (3:1 at 235 oC), and 80.21% (5:1 at 23oC) with yields of 71.82%, 70.31%, and 68.23%. Keywords: citronella oil, purification, rhodinol, spinning band distillation